Antenatal diagnosis of midgut volvulus with successful immediate post-natal management - Zhen Quan Teo; Gordon Thomas; Ronaldo Levy; Thushari I. Alahakoon (Elsevier, 2018)
Fetal volvulus of the midgut occurs when the bowel twists around the axis of the superior mesenteric artery. It is usually diagnosed postnatally but with improving ultrasonography, there have been increasing number of cases reporting antenatal diagnosis that had allowed planning of obstetric intervention and prompt surgery in the postnatal period. We present a case of dichorionic diamniotic twin pregnancy wherein Twin A had multiple anomalies, which included an Ivemark heterotaxy syndrome with a double outlet right ventricle. This twin developed dilated bowel loops at 33 weeks of gestation. The pregnancy continued to have regular antenatal surveillance and was managed by a multidisciplinary team. At 36 weeks of gestation, these bowel loops were found to have absence of peristalsis compared to previous ultrasounds. An emergency caesarean section was performed, which was uncomplicated and Twin A weighing 2760g was born with Apgars of 61 and 85. The diagnosis of volvulus in Twin A was confirmed during its emergency laparotomy along with a Type IV jejunal atresia and was successfully treated surgically with resection and administration of tissue plasminogen activator (TPA). This is the first description of a case treated with TPA after fetal diagnosis. Keywords: Volvulus, Antenatal diagnosis, Tissue plasminogen activator, Congenital anomalies